China's military presence in the South China Sea and the AUKUS alliance on Indonesia's defense strategy: A review of the land defence aspects - Sukma Wijaya; Joni Widjayanto; Wayan Nuriada (Strategi Perang Semesta, 2022)
As its economy developed, China managed to improve the combat capabilities of its military and defense industry. The presence of China as a new power that has the potential to become hegemony in the region, has caused anxiety for countries in Southeast Asia.  Complexity in the region grew after the United States, Britain and Australia formed a new military alliance "AUKUS" in 2021.  The research method used is qualitative descriptive, according to Sugiyono, descriptive method is research that describes the state of the object being studied as it is, according to the situation and conditions when the research is carried out. Theories used balance of power, and Stap-to-war.  China's military modernization makes the country strong and has the potential to become hegemony in the region. This situation prompted the region's country to improve its military capabilities, produce weaponry and military equipment, and even form military alliances.  The AUKUS is a balance of power to offset China's influence, by building nuclear-powered submarines, and is currently developing mach-5 hypersonic missiles.  The U.S.-China rivalry makes the LCS region a single geostrategic theater. Indonesia implements an active defense strategy, with pays attention to aspects of geographical conditions as an island nation.